LIGHTWEIGHT DESIGN OF A SMALL FAMILY CAR DISC BRAKE BASED ON ANSYS (MT) - WANG SuoGuo; SHEN JingHu; SHI Le (Jixie qiangdu)
Aiming at the lightweight design of the disc brake for small family cars, the finite element analysis and multi-objective optimization of the disc brake were carried out.Through the sensitivity analysis, the contribution degree of each size parameter of the brake disc to the braking performance and quality was established, and the optimization variables were quickly selected.Taking the lightest weight of the brake disc, the lowest surface temperature of the brake disc and the minimum maximum equivalent stress as the objective function, a multi-objective optimization mathematical model was established. NSGA-II hybrid variant algorithm based on the control elite strategy in Ansys was used to optimize the brake disc. After the optimization, the quality of the brake disc is reduced by 29.2% by simulation. The correctness of the simulation results is verified by the experiment under the same working condition, which realizes the lightweight of the brake disc and provides a reference for the design of the disc brake.